Exposing ESP Teacher’s and Students’ Perception about Teaching Speaking for Tourism Program - Khoirunnisa, Khoirunnisa; Suparno, Suparno; Supriyadi, Slamet (Dinamika Ilmu, 2018)
This study was framed in English for Spesific Purposes to look into the teacher’s and students’ perception about teaching speaking for Tourism Program. To this end, ten male and female Tourism students and their English teacher in one of private Vocational High School in Surakarta were purposively selected as the participants in this study. They were invited to take part in semi-structured interview. The findings showed that English for Tourism emphasizes more in building students’ speaking skill. All participants shared their positive perceptions toward teaching speaking for Tourism Program. The students perceived that speaking was very crucial for them since it gave such impact to their future career. Nevertheless, there were several difficulties students faced in the learning process including grammar, pronunciation, vocabulary, content. There were also some challenges such as lack of confidence, low motivation and limited learning material. However, both teacher and students were actively involved in overcoming those barriers. This study shed light on the importance of collaboration between teacher and students. It is suggested that they should work closely to improve the quality of ESP program.